Climate Change Impacts in Soil- Water Balance in Semi-Arid Region, Southeast of Spain: The use of Eco- Hydrological Model - Issam Touhami; Esteban Chirino; José Miguel Andreu; Hassane Moutahir; Juan Rafael Sánchez; Juan Bellot (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2017)
Predictions of climate change have a high interest in semiarid regions like the province of Alicante (SE Spain). It is expected that the decrease of precipitation and the increase of air temperature according to climate change forecasts, could impact on the recharge to aquifers. In this context, the aim of this study was explore the possible impact of climate changes forecasts on recharge in a small aquifer southeastern Spain. Air temperature and precipitation data in two climate change scenarios, B2-low and A2-high have been coupled to HYDROBAL model. The HYDROBAL software is a useful eco-hydrological model with daily resolution for assessing water balances in different vegetation types in a semiarid region of southeastern Spain. Based on two models, HYDROBAL and DISRUM, water balance was calculated on two scales (vegetation plots and watershed). Over the latter period (2071-2099), we expect reduced average annual groundwater recharge, of up to 17% (49 mm), if compared to the baseline period (1961-1990).